Application of 1-MCP to Intact Tomatoes Differing in Maturity Delays Quality Changes in the Stored Slices - Darwin Habinsaran Pangaribuan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
A study was carried out to determine the effect of 1-MCP applied to intact tomatoes differing in maturity stage onquality of stored tomato slices. 1-MCP (1 μL L-1, 20 °C, 12 h) was applied directly to intact tomatoes from ‘turning’, ‘pink’,and ‘light-red’ stages of maturity. After slicing, slices were stored for up to 10 days at 5 ºC. 1-MCP maintained slice qualityduring storage following treatment of intact ‘turning’ and ‘pink’ maturity fruit as indicated by higher titratable acidity, higherascorbic acid concentration, and lower lycopene content.1-MCP treatment did not signifi cantly affect soluble solids andelectrolyte leakage. Slices from ‘light-red’ maturity stage fruit did not respond to 1-MCP. The results show that applicationof 1-MCP to intact tomatoes was effective in maintaining tomato slice quality if 1-MCP is applied to fruit at early (‘turning’and ‘pink’) stages of maturity.Keywords: 1-methylcyclopropene, soluble solids, acidity, ascorbic acid, lycopene, electrolyte leakage